Patency of Reverse Saphenous Vein Graft for Revascularization of Lower Limbs in Diabetic Patients - Mohammad Iqbal Khan; Habib ur Rahman; Naveed Mufti (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
Objectives: Diabetic patients are prone to early development of vasculopathy, resulting in lower limb ischemia, which can lead to non-healing ulcers, foot infection, loss of limb, and even death. These patients need revascularization of their limb either using endovascular or open surgical techniques.Not all patients are suitable for endovascular treatment warranting the open surgical revascularization techniques. The objective of this study was to evaluate the patency of arterial bypass grafting using reverse saphenous vein graft in the treatment of peripheral vascular disease of the lower limbs in diabetic patients. Patients and Methods: Between January 2004 and December 2014, 218 diabetic patients with lower limb ischemia of Fontaine class III and IV underwent distal arterial bypass grafting with autologous reverse saphenous vein graft. Another group of 103 patients where the saphenous vein was ether previously used or not suitable as conduit underwent revascularization using synthetic ePTFE graft. Patency of the grafts, overall effectiveness of revascularization, improvement in symptoms, and healing of ulcers were assessed at short-term (three months) and long-term (mean 20.6 ±6.6 months) follow-up.